Panayiotopoulos syndrome: A benign childhood epilepsy syndrome masquerading as head injury - Srivastava, Preeti; Mishra, Sudhir (Indian Journal of Child Health, 2020)
Panayiotopoulos syndrome (PS) is a benign childhood epilepsy syndrome characterized by autonomic seizures and electroencephalogram (EEG) showing predominant occipital paroxysms. PS may easily be confused with many non-epileptic conditions such as atypical migraine, gastroenteritis, or syncope. We here present a 5 ½-year-old boy who presented to us with a history of head injury followed by vomiting, seizures, and prolonged unresponsiveness. Neuroimaging was normal, and on detailed history, it was clear that autonomic symptoms preceded the head injury and so an EEG was done. Interictal EEG showed bilateral occipital spikes and wave discharges with characteristic “fixation-off sensitivity.” Hence, the seizure semiology along with the EEG pattern helped to clinch the diagnosis. Parents were counseled about the benign nature of the condition